Philosophers and Economists Can Agree on the Intergenerational Discount Rate and Climate Policy Paths - Frikk Nesje; Moritz A. Drupp; Mark C. Freeman; Ben Groom (Center for Economic Studies and ifo Institute (CESifo), 2022)
The estimated values to society from long-term public projects, including climate change mitigation and infrastructure construction, are highly sensitive to the social discount rate (SDR) employed. Governmental guidance on social discounting has predominantly been based on input from expert economists. It is not clear, however, that economists possess any special expertise on the ethical issues that underpin long-term societal decision-making. This study compares expert economists' views on key components of the long-term SDR with those of a disciplinary group of experts who may be deemed most trained on ethical matters: philosophers. The results indicate that both expert groups provide surprisingly similar recommendations on these components and on the SDR itself, with a real SDR recommendation of 2% receiving most support in both disciplines. An analysis of qualitative remarks shows areas of broad agreement and yet distinct differences in rationales. While economists provide numerous technical extensions within a consequentialist Discounted Utilitarian approach, philosophers advocate more strongly for alternative ethical approaches to standard Utilitarian calculus. In the politicized world of long-term decision-making, this paper illustrates how more inclusive and deliberative approaches to complex issues such as intergenerational justice can guide more nuanced decision-making today and lead to multidisciplinary support for climate action.
Keywords: C83; D61; H43; Q58; 330; intergenerational social discounting; expert survey; philosophy; economics; climate policy